(3GdbUjOI GdefaQLIs - (3jhSa Hf eMeO Hf jhSa GdJhRQj , GdJdeSGfj, CHh GdaVd, GHf GdfMhqj,J (B513 (3g` s
(3ChdgG (B:s
(3GTJOj CReI JfaQLj bO CPf djdc HGdHdL s
(3BNQgG (B:s
(3hGTQH JSfje eYLRgG dG eeJRLkG hHeeJRL s
(3NeSI hKdGKjf HjJkGs
(3hQO CjVkG JMJ Qbe (B2185s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B247 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B334s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B125 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1346s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs